MICROSURGICAL RECONSTRUCTION OF THE ORAL CAVITY IN PATIENTS WITH ONCOLOGICAL DISEASES - Jumaev, A.U.; Dustov, Sh.Kh; Saidov, G.N. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: Improving the functional results of microsurgical reconstruction of the tongue after radical oncological operations. Material and methods: In the Department of Neck Head Tumors and Reconstructive Surgery, Bukhara Regional Branch of the Republican Specialized Scientific and Practical Medical Center for Oncology and Radiology, in the period 2017-2019, surgical treatment was performed for ten patients with tongue cancer with plastic skin and fascial radial graft from the forearm using microsurgical technique. In nine patients with a diagnosis of cancer of the lateral surface of the tongue, T1-2N0-1M0 stages were detected and in one patient T3N1M0 stages were detected. All patients underwent surgical treatment in the amount of: hemiglosectomy, cervical lymphadenectomy and microsurgical plastic surgery of the tongue with reinnervated, skin-fascial radial graft from the forearm. Microsurgical plastic surgery was performed simultaneously for one patient with a diagnosis of T1N0M0, and in other cases, at the first stage, 2-4 courses of polychemotherapy were performed according to the scheme: Cisplatin 75 mg / m2, fluorouracil 750 mg / m2 or chemoradiotherapy and after partial regression of the tumor in the second stage, surgical treatment and restoration of the tongue. Results: The observation period ranged from 2 to 22 months. The overall survival of the flap was 80%. In two cases in the postoperative period, flap necrosis was detected. In one patient, after 6 days of surgery, arterial thrombosis of a microvascular anastomosis was found, with which the flap was removed, in the second after 10 days due to suppuration after the surgical wound, the flap was removed. The average healing time for the region of the donor forearm was 4 weeks. Conclusion: Our first experience shows that microsurgical reconstruction of the tongue is a good reconstructive option for patients and improves the functional qualities of patients after surgery in terms of speech, chewing and swallowing.